Aviation Information Network Architecture Based on SDN/NFV - Xinkang SONG; Xiang WANG; Haotong FU; Shanghong ZHAO (天地一体化信息网络)
As the key support for the emergence of cluster combat eff ectiveness, the design architecture of aviation information network will infl uence the combat mode in the aviation fi eld.Based on the future operational requirements of aviation cluster, the defi ciency of traditional aviation information network was introduced and the technical characteristics of SDN/NFV was analyzed.On this basis, combined SDN/NFV technology and aviation information network, an aviation information network architecture based on SDN/NFV was proposed, and its components were briefl y described.The future research directions and challenges of aviation information network architecture based on SDN/NFV were summarized.It also explored the ability of establishing effi cient information exchange and fi ne-grained aggregation of resources in aviation information network, which provided reference for the development of aviation information network in the future.